A Configurational Analysis of the Impact of Entrepreneurial Orientation and Global Mindset on Export Performance of Smes - Matemane, R.; Mintah, R.; Şahin, F.; Karadağ, H. (SAGE Publications Inc., 2024)
Although contemporary literature provides several important insights into the role of attributes of SMEs, there is much less evidence on what configuration of entrepreneurial orientation and global mindset makes this process successful, that is, contributing to the export performance of SMEs. This study uses a fuzzy set qualitative comparative analysis on a sample of 97 SMEs in Ghana to explore the potential complementary role between the entrepreneurial orientation dimensions and global mindset for superior export performance. The results indicate two different yet equifinal configurations of these factors that lead to a high level of export performance of SMEs. One of the configurations shows that proactive and innovative SMEs with managers high on global mindset achieve superior export performance regardless of their willingness to take risks. Another configuration indicates that regardless of the global mindset of managers, SMEs can achieve higher export performance by being proactive, innovative, and willing to take high risks. Several implications for theory and practice are discussed based on the findings. © The Author(s) 2024.
Keywords: Entrepreneurial Orientation; Export Performance; Fuzzy Set Qualitative Comparative Analysis; Global Mindset; Smes